Sistemática filogenética dos primatas do novo mundo e a evolução do aparelho mastigatório (Platyrrhini, Primates) - Guedes, Patrícia Gonçalves (2000)
Studied the evolution of the masticatory apparatus of the New World monkeys as part of a broader cladistic research program on primate evolution. All the 16 currently recognized extant genera currently plus 4 fossil taxa were investigated. The information content in this morphological complex is summarized in 80 hypotheses of primary homology. Additionally, the final matrix also included 25 biological attributes assembled by HOROVITZ (1990), bringing a total of 131 transformation series. The branch swapping algorithm was chosen for the heuristic parsimony analysis (m* bb* - Hennig86 software). All characters were treated as unorder and Aegyptopithecus was used as the rooting reference. The analysis yielded 40 equally parsimonious trees (289 steps, CI = 0.48 and RI = 0.67). Howevre, after using the successive weighting option, the reanalysis os the same data matrix resulted on a single tree (889 steps, CI = 72 and RI= 85) that was considered the major result of the Thesis. Under parenthetic notation the hierarchy of this tree may be presented as follows: (Aegyptopithecus Pygathrix (((Pithecia (Chiropotes Cacajao) ((Brachyteles (Alouatta Stironia)) (Lagothrix (Caipora (Ateies Protopithecus)))) (((Aotus Calcebus) (Cebus (Saimiri Carlocebus)) (Calmico (Saguinus (Leontopithecus (Callithrix gr. jachus (Cebuela Callithrix gr. arentata))))). A significant par of these relationships suppored several previous morphological and even molecular analysis. lt should be noted that for the first time Prtopitecus and Caipora were included in a cladistic analysis, and were found to be associated to the atelid phylogenetic context.